Training of Utilization of Coconut Dregs Flour and Its Processed Product to Increase Fiber Consumption in Tumpatan Village, Beringin Sub-District - Bakara, Tiar Lince; Tarigan, Novriani (Talenta Publisher Universitas Sumatera Utara, 2018)
The average national proportion of fewer-vegetables consumption for the population above 10 years is around 93.5%. Fiber can be obtained from fruits, vegetables, and coconut dregs which can be processed into various types of food. The utilization of coconut dregs as a source of fiber has not been revealed much and has been only used as animal feed and â€œtempebongkrekâ€. The main purpose of this community service was to improve skills of women cadres and members of PKKgroup about how to processcoconut dregs into brownies, cookies, and steamed cakes.The community service activities were conducted from March to September 2017 in Tumpatan Village, Beringin Sub-District. The activities consisted of three stages: pre-intervention, intervention, and post-intervention. In the intervention stage, some activities conducted were including training, socialization, and cooking demonstration of brownies, cookies, and steamed cakes. Based on the results of the intervention, the women cadres and members of PKK groupunderstood the benefits and functions of processed coconut dregs flour, and the advantages of food using coconut dregs flour. In addition, the women cadres andmembers of PKK group would be able to process coconut dregs and make snacks, such as brownies, cookies, and steamed cakes. The training activities of coconut dregs processing improved skills of the women cadres and members of PKK group in utilizing materials which have not been widely used as food ingredients.